Pengaruh Kualitas Produk dan Inovasi Digital Marketing Terhadap Keputusan Pembelian Ulang Pelanggan Mcdonald’s - Rolando, Benediktus; Dea, Alhima Nurmala (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to analyze the impact of product quality and digital marketing innovation on the repurchase decisions of McDonald's customers in Indonesia. Employing a quantitative approach with a survey method, data were collected through online questionnaires distributed to McDonald's customers. The collected data were analyzed using multiple linear regression to determine the influence of product quality and digital marketing innovation on repurchase decisions. The research results indicate that product quality has a positive and significant effect on repurchase decisions, with a regression coefficient of 0.45 and a p-value < 0.05. This means that the better the product quality, the higher the likelihood of customers making repeat purchases. Additionally, digital marketing innovation also has a positive and significant effect, with a regression coefficient of 0.38 and a p-value < 0.05. This suggests that more innovative digital marketing strategies lead to higher customer repurchase decisions. The regression model shows a good fit with an Adjusted R² of 0.62, indicating that 62% of the variation in repurchase decisions can be explained by product quality and digital marketing innovation. This research contributes to the development of marketing theory by highlighting significant factors influencing repurchase decisions. Practically, the findings provide managerial implications for McDonald's to enhance product quality and digital marketing innovation as strategies to boost customer repurchase decisions. By optimizing the use of digital technology in marketing activities and ensuring product quality that meets customer expectations, McDonald's can maintain and increase customer loyalty through repurchases.